2003
DOI: 10.1093/hmg/ddg074
|View full text |Cite
|
Sign up to set email alerts
|

Aggresomes protect cells by enhancing the degradation of toxic polyglutamine-containing protein

Abstract: Expression of misfolded protein in cultured cells frequently leads to the formation of juxtanuclear inclusions that have been termed 'aggresomes'. Aggresome formation is an active cellular response that involves trafficking of the offending protein along microtubules, reorganization of intermediate filaments and recruitment of components of the ubiquitin proteasome system. Whether aggresomes are benevolent or noxious is unknown, but they are of particular interest because of the appearance of similar inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
281
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(305 citation statements)
references
References 27 publications
22
281
1
1
Order By: Relevance
“…[77][78][79] In several aggregating-protein disease models, autophagy is implicated in degrading or preventing the formation of protein inclusions. 20,[80][81][82][83] We do not have evidence that the intracellular Aβ-deposits observed in our model 32 are the targeted cargo of autophagosomes (at least not in their entirety) because they are generally much larger than even the largest observed autophagosomes. This interpretation agrees with reports that polyglutamine and polyalanine protein inclusions are larger than autophagosomes and thus are incompatible as their cargo.…”
Section: Do Not Distributementioning
confidence: 66%
“…[77][78][79] In several aggregating-protein disease models, autophagy is implicated in degrading or preventing the formation of protein inclusions. 20,[80][81][82][83] We do not have evidence that the intracellular Aβ-deposits observed in our model 32 are the targeted cargo of autophagosomes (at least not in their entirety) because they are generally much larger than even the largest observed autophagosomes. This interpretation agrees with reports that polyglutamine and polyalanine protein inclusions are larger than autophagosomes and thus are incompatible as their cargo.…”
Section: Do Not Distributementioning
confidence: 66%
“…5,139,140 Being too large to be disposed of by the proteasomes, such aggregates are often sequestered by macroautophagy and delivered to the lysosomes. [141][142][143][144][145] It would not be unreasonable to assume that membrane-bound Hsc70 and sHsc70 could help phagophores to recognize denatured proteins and thus initiate the autophagic sequestration of protein aggregates. The well-documented association of Hsc70 with large protein aggregates in general 139,140,146 might in fact reflect the presence of recruited phagophores, a possibility supported by the assembly of membrane vesicles and cisternae 147,148 and of the autophagic membrane marker, LC3, 145,148,149 in the periphery of such aggregates.…”
Section: Autophagosomal Membrane Proteinsmentioning
confidence: 99%
“…Aggresome can be formed as the consequence of overwhelmed proteasome system or of cellular response to mutant or misfolded proteins. 30,32 Apparently, the formation of aggresome is a cellular protective mechanism to sequester potentially toxic protein aggregates that are scattered around the intracellular milieu or to deliver them for disposal through an alternative pathway such as autophagosome. Many nuclear proteins undergo cytoplasmic degradation as an integral part of normal cellular regulatory process.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The components of aggresome include ubiquitin, subunits of the 20S proteasome and intermediate filament vimentin, suggesting that aggresome could serve as an alternative proteolysis center of the cellular system. 31,32 Recent studies have demonstrated that aggresome is indeed not just a sequester area for misfolded protein aggregates, rather an integral part of normal cellular regulatory process to control the levels of targeted proteins in response to specific stimuli. 33,34 In this report, we describe the molecular mechanisms that regulate the activity of transcriptional coactivator p300.…”
Section: Introductionmentioning
confidence: 99%